Cow gore related orofacial injuries: a review of cases managed at a semi-urban Hospital in Nigeria - Babatunde O. Bamgbose; Thomas Owobu; Basil T. Ojukwu; Auwal S. Balarabe (Journal of Dentomaxillofacial Science, 2020)
Objective: This study reviewed such cases with oro- facial injuries as presented at the hospital for the period of seven years.Material and Methods: The study sample size consists of a total of 22 patients who had various degrees of orofacial injuries were seen and managed during the period of study. Although some of the case were considered severe, there was no fatality recorded during the period under review. Some patients with soft tissues avulsion at any part of the body revealed jagged wound edges and, in some cases, the wounds were still bleeding at the time of presentation.Results: A total of 22 patients of which 19 were males (86.36%) and 3 females (13.64%) were received and treated at the Oral and Maxillofacial department during the period under review. A gender ratio of male to female, 6.33 :1, was recorded. 14(63.64%) of the number had fracture of oro-facial bone.  The data were analyzed using statistical package for social sciences (SPSS) version 20.0 (SPSS Inc, Chicago, IL).Conclusion: Farm safety experts estimate that more than half of cow injuries can be prevented by using some type of personal protective equipment, depending on the work activity. Unfortunately, most herders in developing world does not have this protective equipment thereby increasing the risk or frequently sustaining injuries from cow attacks.